2015
DOI: 10.1016/j.ajhg.2015.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Effects of Colocalizing Genomic Annotations to Functionally Prioritize Non-coding Variants within Complex-Trait Loci

Abstract: Identifying genomic annotations that differentiate causal from trait-associated variants is essential to fine mapping disease loci. Although many studies have identified non-coding functional annotations that overlap disease-associated variants, these annotations often colocalize, complicating the ability to use these annotations for fine mapping causal variation. We developed a statistical approach (Genomic Annotation Shifter [GoShifter]) to assess whether enriched annotations are able to prioritize causal va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 61 publications
(125 reference statements)
6
124
0
2
Order By: Relevance
“…For 35 CS variants (out of 186 variants from 17 loci; 18.8%), we identified an overlap with hematopoietic NDRs, a significant enrichment compared with non-CS variants in moderate to high LD (r 2 > 0.5) (OR = 2.41, P = 0.0009). Additionally, a permutation test involving local shifting of the NDRs around the CS variants revealed a significant enrichment (1.87-fold change in overlap, P = 0.00042) (28). Furthermore, at 11 of 13 independent loci (85%), at least one CS variant overlapped a NDR ( Fig.…”
Section: −15mentioning
confidence: 99%
“…For 35 CS variants (out of 186 variants from 17 loci; 18.8%), we identified an overlap with hematopoietic NDRs, a significant enrichment compared with non-CS variants in moderate to high LD (r 2 > 0.5) (OR = 2.41, P = 0.0009). Additionally, a permutation test involving local shifting of the NDRs around the CS variants revealed a significant enrichment (1.87-fold change in overlap, P = 0.00042) (28). Furthermore, at 11 of 13 independent loci (85%), at least one CS variant overlapped a NDR ( Fig.…”
Section: −15mentioning
confidence: 99%
“…However, current methods that aim to evaluate the contribution of such regions to genetic variation in disease cannot always do so robustly or are not readily applicable for systematic analysis and comparison of broad sets of features. In particular, it has been shown that LD, gene density and MAF can confound enrichment analysis results 12 . Here we further estimated the relative effect of each of those features and identified LD as the largest confounder.…”
Section: Discussionmentioning
confidence: 99%
“…In their simpler implementation, they estimate enrichment of association p--values based on comparisons of the full set of genetic variants analysed in the GWAS study [9][10][11] , or on subsets of highly associated variants, for instance variants achieving genome--wide significance [12][13][14] . These approaches have identified many biologically plausible patterns of correlation (for instance in open chromatin marks for lipid traits in liver cell types and Crohn's disease in immune cells) and are broadly used for ranking the relative contribution of features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If considering LD is crucial, we refer the user to the GoShifter enrichment tool (Trynka et al, 2015) that uses LD information from the Phase I 1000 genomes data release and estimates enrichments by local permutations. However, regulatory similarities among the 39 disease/trait-associated SNP sets obtained with GoShifter correlated less well with the shared genomic loci similarities (Supplementary Table S4).…”
Section: Discussionmentioning
confidence: 99%